2003
DOI: 10.1091/mbc.e02-07-0451
|View full text |Cite
|
Sign up to set email alerts
|

MyoD Distal Regulatory Region Contains an SRF Binding CArG Element Required for MyoD Expression in Skeletal Myoblasts and during Muscle Regeneration

Abstract: We show here that the distal regulatory region (DRR) of the mouse and human MyoD gene contains a conserved SRF binding CArG-like element. In electrophoretic mobility shift assays with myoblast nuclear extracts, this CArG sequence, although slightly divergent, bound two complexes containing, respectively, the transcription factor YY1 and SRF associated with the acetyltransferase CBP and members of C/EBP family. A single nucleotide mutation in the MyoD-CArG element suppressed binding of both SRF and YY1 complexe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(71 citation statements)
references
References 60 publications
5
65
0
Order By: Relevance
“…49,50 This observation may be explained by the fact that SRF and MRTF factors have been detected in the interstitial cells that line the vasculature, which are absent in undifferentiated MSCs before myogenic differentiation. 51,52 The induction of miR199a-5p expression levels, coinciding with increased SRF expression during myogenic differentiation, further supports the hypothesis that SRF is a regulator of muscle hypertrophic growth while suppressing MSC proliferation. 25 Recently, it has been shown that induction of WNT7a can induce muscle hypertrophy by activating the PI3K/AKT pathway in myofibers.…”
Section: Discussionsupporting
confidence: 57%
“…49,50 This observation may be explained by the fact that SRF and MRTF factors have been detected in the interstitial cells that line the vasculature, which are absent in undifferentiated MSCs before myogenic differentiation. 51,52 The induction of miR199a-5p expression levels, coinciding with increased SRF expression during myogenic differentiation, further supports the hypothesis that SRF is a regulator of muscle hypertrophic growth while suppressing MSC proliferation. 25 Recently, it has been shown that induction of WNT7a can induce muscle hypertrophy by activating the PI3K/AKT pathway in myofibers.…”
Section: Discussionsupporting
confidence: 57%
“…5C-E Δ13 muscles, compared with wt levels. With these data, and because Srf is one of the main transcription factors controlling Myod expression in muscle (Gauthier-Rouviere et al, 1996;L'honore et al, 2003), we propose as a working hypothesis that Igf2 controls Myod expression by downregulating Srf, possibly via the production of miR-483.…”
Section: Research Articlementioning
confidence: 84%
“…Recently, a microRNA, miR-483-5p, the gene for which is embedded in intron 2 of Igf2, has been shown to target the 3ЈUTR of serum response factor (Srf) (Qiao et al, 2011). The transcription factor Srf is one of the factors responsible for the activation of Myod expression (Gauthier-Rouviere et al, 1996;L'honore et al, 2003). Nevertheless, little is known in vivo about the role of Igf2 in skeletal muscle development and about potential interactions between Myod and Igf2.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic deletions of Mrf4, MyoD or Myf5 alone do not produce overt defects in sarcomere formation in mice Rawls et al, 1998;Rudnicki et al, 1992), whereas genetic deletion of myogenin causes perinatal lethality due to a complete lack of myoblast fusion and myofiber formation (Hasty et al, 1993;Nabeshima et al, 1993). MyoD has also been shown to associate directly with SRF and to serve as a co-activator of SRF-dependent muscle genes (L'Honore et al, 2003). Interestingly, the MRTF dKO phenotype is more severe than the phenotypes of mice with single deletions of MyoD, Myf5 or Mrf4.…”
Section: Discussionmentioning
confidence: 99%